State corporatism and proto-industry : the Württemberg Black Forest, 1580-1797 - Ogilvie, Sheilagh C. (Cambridge studies in population, economy, and society in past time, 1997)
State Corporatism and Proto-Industry focuses on an industrial countryside in south-west Germany, where a dense worsted industry dominated the rural economy from 1580 to 1800. This is an example of 'proto-industry', the dense, export-oriented rural manufacturing which arose throughout Europe before factory industrialization. But although the Württemberg worsted industry possessed all the features of a classic proto-industry, closer scrutiny throws doubt on basic assumptions about European proto-industrialization. In this book, Sheilagh Ogilvie shows that proto-industries did not break down traditional society. Instead, corporate institutions such as guilds, merchant companies, village communities and manorial systems retained enormous power. This was a result of 'state corporatism': the expanding early modern state granted privileges to favoured groups in return for fiscal and regulatory co-operation. As Ogilvie shows, these corporate privileges profoundly constrained both individual decisions and economic development.